Improving Process Evaluations of Health Behavior Interventions: Learning From the Social Sciences. (September 2015) - Morgan-Trimmer, Sarah
This article reflects on the current state of process evaluations of health behavior interventions and argues that evaluation practice in this area could be improved by drawing on the social science literature to a greater degree. While process evaluations of health behavior interventions have increasingly engaged with the social world and sociological aspects of interventions, there has been a lag in applying relevant and potentially useful approaches from the social sciences. This has limited the scope for health behavior process evaluations to address pertinent contextual issues and methodological challenges. Three aspects of process evaluations are discussed: the incorporation of contexts of interventions; engagement with the concept of "process" in process evaluation; and working with theory to understand interventions. Following on from this, the article also comments on the need for new methodologies and on the implications for addressing health inequalities.